بيع الذىب بين الضوابط الشرعية والممارسات العممية - غربي, آمنة; معيوة, بشيرة; بالي, سارة (University of Eloued-جامعة الوادي, 2015)
تعالج ىذه الد ا رسة مكضكع مف المكاضيع التي تتعمؽ بممارسات الناس اليكمية المتعمقة ببيع الذىب بيف الضكابط الشرعية كالممارسات العممية، كابتدأت الد ا رسة مف إشكالية تدكر حكؿ مدل تطبيؽ الباعة )الصُّياغ( الضكابط الشرعية عند بيعي لمذىب، كىذا انطلاقا مف أف الذىب يمتاز بصفة النقدية فيو، كقسمت الد ا رسة إلى ثلاثة مباحث: مبحث تمييدم كت التطرؽ فيو إلى مفيك الذىب كأنكاعو كبياف نشأة النقدية فيو، كأما المبحث الأكؿ تناكلنا فيو الضكابط الفقيية لبيع الذىب، كختمنا بمبحث ثاني كفيو د ا رسة ميدانية عف طريؽ الاستبياف لمممارسات العممية لبيع الذىب، كخمصت الد ا رسة إلى أف أغمب الصُّياغ لا يطبقكف الضكابط الشرعية في بيعي لمذىب. abstract This study addressed the subject of topics which are related the practices of everyday people related the sale of gold between legitimate controls, practices. the study began issue revolves about the extent of the application vendors (jewelers) The are controls at the sale of gold. And start this is the basis of that gold is characterized in cash in it. The study is divided into three sections: Study of introductory was the address to the definition of gold, types and statement of cash genesis of it, and the first topic we addressed the doctrinal controls for the sale of gold, and we ended second a field study by questionnaire practices way for the sale of gold, and the study concluded that most jewelers do not apply exat in the sale of gold.
مذكرة ليسانس
Keywords: الذىب/ الضوابط الشرعية/ والممارسات العممية; Or / Contrôles de la charia / pratiques pratiques